2021
DOI: 10.1590/1414-431x2021e11499
|View full text |Cite
|
Sign up to set email alerts
|

Hashtag bone: detrimental effects on bone contrast with metabolic benefits one and five years after Roux-en-Y gastric bypass

Abstract: Bone loss is a potential adverse consequence of rapid and sustained weight loss after bariatric surgery. The aim of the present study was to evaluate the bone mass, body fat distribution, and metabolic parameters in women submitted to Roux-en-Y gastric bypass (RYGB). The study included the following three groups: one group of lean women (control [C] group) and two groups of obese women, one evaluated one year (B1) and the other five years (B5) after RYGB. Dual-energy X-ray absorptiometry and magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…There is a paucity of prospective data evaluating both the bone loss and metabolic benefits of bariatric surgery in severely obese individuals ( 72 ). However, a recent cross-sectional study has shown metabolic benefits obtained with bariatric surgery, which persist for 5 years after the procedure, even in patients whose BMI remains in the range of obesity.…”
Section: Weight Loss After Surgical Interventions In the Gastrointest...mentioning
confidence: 99%
See 3 more Smart Citations
“…There is a paucity of prospective data evaluating both the bone loss and metabolic benefits of bariatric surgery in severely obese individuals ( 72 ). However, a recent cross-sectional study has shown metabolic benefits obtained with bariatric surgery, which persist for 5 years after the procedure, even in patients whose BMI remains in the range of obesity.…”
Section: Weight Loss After Surgical Interventions In the Gastrointest...mentioning
confidence: 99%
“…After bariatric surgery, the VAT/SAT distribution ratio and the amount of IHL were similar in individuals with obesity or normal weight. In contrast, individuals submitted to bariatric surgery present early elevation of remodeling marker of bone resorption, a pattern that is maintained for at least 5 years after surgery ( 72 ). Two previous studies, one cross-sectional ( 72 ) and the other prospective ( 73 ), have suggested precocious and sustained increased levels of the biochemical marker of bone resorption CTX.…”
Section: Weight Loss After Surgical Interventions In the Gastrointest...mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple pieces of evidence indicate that not only muscle and adipose tissue contribute to the regulation of energy metabolism but that peptides produced by bone cells are also part of the orchestration that involves the metabolic control of glucose, lipids, and proteins (1)(2)(3). Similarly, several hormones are important for the regulation of energy metabolism and influence bone remodeling (e.g., insulin and epinephrine).…”
Section: Introductionmentioning
confidence: 99%